2012
DOI: 10.1084/jem.20112741
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 1 forms negative costimulatory microclusters that directly inhibit T cell receptor signaling by recruiting phosphatase SHP2

Abstract: After encounter with its ligand, PD-1 translocates into TCR microclusters, where it transiently recruits SHP2 and suppresses phosphorylation of TCR signaling components and TCR-driven stop signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
680
5
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(743 citation statements)
references
References 51 publications
43
680
5
15
Order By: Relevance
“…2D). Since PD-1 is known to mediate its inhibitory function in T cells by increasing TcR activation threshold through the regulation of early TcR signaling [23], our data supported the notion that miR-155 expression in adaptively tolerant T cells was conditioned directly by TcR signals. This assumption was verified by stimulating in vitro purified adaptively tolerant T cells in the presence of varying concentrations of immobilized PD-L1-Ig.…”
Section: Mir-155 Is Strongly Expressed By Adaptively Tolerant Cd4 + Tsupporting
confidence: 81%
“…2D). Since PD-1 is known to mediate its inhibitory function in T cells by increasing TcR activation threshold through the regulation of early TcR signaling [23], our data supported the notion that miR-155 expression in adaptively tolerant T cells was conditioned directly by TcR signals. This assumption was verified by stimulating in vitro purified adaptively tolerant T cells in the presence of varying concentrations of immobilized PD-L1-Ig.…”
Section: Mir-155 Is Strongly Expressed By Adaptively Tolerant Cd4 + Tsupporting
confidence: 81%
“…However, recent studies using single-cell imaging demonstrate that on ligation with its ligand, PD-1 clusters with the TCR and transiently associates with the phosphatase SHP2, resulting in dephosphorylation of signaling molecules and direct inhibition of T-cell activation (38). Importantly, this PD-1-mediated inhibitory mechanism was apparent in T cells activated in vitro and PD-1 hi T cells generated in vivo (38). We hypothesize that transient expression of PD-1 induced by antigen exposure in a vaccination setting may be an immunoregulatory mechanism contributing to contraction of the M72-specific effector CD4 T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented the usage of costimulatory molecule as an antitumor immunotherapy to trigger and enhance strong T-cell response against tumor by different combination approaches (Xiao et al, 2007). Programmed death-1(PD-1) is the type I transmembrane immunoinhibitory receptor expressed on activated T and B cells, consist of single extracellular Ig-like variable (IgV) domain and an intercellular part contains an immunoreceptor tyrosine-based inhibitory motif (Xu et al, 2006), which delivers negative signals upon ligation to its two ligands B7-H1 and B7-DC (Youngnak et al, 2003;Yokosuka et al, 2012). PD-L1 a recently identified coinhibitory molecule belonging to the B7 family molecules (Lee et al, 2005), it is expressed in cells of lymphocyte lineage and is also found in the tissues of various organs, including non-lymphoid organs, such as the heart, lung, placenta, kidney, and liver and several tumor cell lines (Freeman et al, 2000;Paterson et al, 2011), and it can promote the apoptosis of tumor specific CTL and leads to immune evasion of tumor (Dong et al, 2003;Wong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%